2012
DOI: 10.4172/2155-6156.s1-006
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina Reverses Histomorphological Changes in Diabetic Osteoporosis in Pioglitazone Treated Rats

Abstract: Aim: The study was undertaken to assess the protective effect of Spirulina fusiform on risk fracture of bone in insulin resistance rat model and pharmacodynamics effects of Pioglitazone with Spirulina in treating hyperglycemia and hyperlipidaemia of insulin resistance rat. Method: For this aim, 30 Wistar albino rats were equally divided into five groups as control (NC), diabetes mellitus (DM), diabetes mellitus + Pioglitazone (DM+P), diabetes mellitus + Spirulina (DM+S), and diabetes mellitus + Pioglitazone + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…11 Spirulina is rich in protein (60–70%) and contains a broad range of nutrients that include B-complex vitamins (vitamin B 12 ), Pro-vitamin (β-carotene), vitamin E, minerals (calcium, chromium and magnesium) and gamma-linolenic acid. 12 In the United Nations world food conference, spirulina was declared as “the best food for tomorrow”, and, in recent years, it has been gaining popularity as a food supplement. Spirulina was reported in a previous study as a powerful anti-viral, anti–cancer, hypo-cholesterolemic and health improvement agent, thus, it is highly promising as an ideal nutraceutical and pharmaceutical ingredient.…”
Section: Introductionmentioning
confidence: 99%
“…11 Spirulina is rich in protein (60–70%) and contains a broad range of nutrients that include B-complex vitamins (vitamin B 12 ), Pro-vitamin (β-carotene), vitamin E, minerals (calcium, chromium and magnesium) and gamma-linolenic acid. 12 In the United Nations world food conference, spirulina was declared as “the best food for tomorrow”, and, in recent years, it has been gaining popularity as a food supplement. Spirulina was reported in a previous study as a powerful anti-viral, anti–cancer, hypo-cholesterolemic and health improvement agent, thus, it is highly promising as an ideal nutraceutical and pharmaceutical ingredient.…”
Section: Introductionmentioning
confidence: 99%
“…Rise in plasma TG and TC, and fall in HDL-C in diabetic animals is due to increased lipolysis in adipose tissue, and decreased the activity of insulin-dependent lipoprotein lipase leading to elevated blood levels of fatty acids, which are available for the synthesis of TG. Pioglitazone enhances lipoprotein lipase activity and insulin sensitivity by increasing the expression and differentiation of adiponectin resulting in reduced TG levels and increased serum HDL-C levels [ 15 , 16 ]. This may provide another explanation for the improvement in insulin sensitivity despite weight gain by pioglitazone.…”
Section: Discussionmentioning
confidence: 99%
“…This might be associated with residual trabeculae of normal thickness [50]. Similarly, Devesh et al [13] reported that the histopathology results of diabetic rats showed destruction of medullary cavity at the expense of the bone tissue thickness and gaps formation in Haversian canals within the bone tissue.…”
Section: Discussionmentioning
confidence: 99%